Percutaneous Alcohol Sclerotherapy of Simple Hepatic Cysts. Results From a Multicentre Survey in Italy. Issue 2 (1994) - Montorsi, Marco; Torzilli, Guido; Fumagalli, Uberto; Bona, Stefano; Rosati, Riccardo; de Simone, Matilde; Rovati, Vittorio; Mosca, Franco; Filice, Carlo
Abstract : The increased use of Ultrasonography (US) has led to increased detection of simple hepatic cysts. For symptomatic cysts treatment is necessary. Until some years ago surgery was the only therapy. We have treated a large number of patients with Percutaneous Alcohol Sclerotherapy (PAS) and evaluated retrospectively the efficacy of this approach. Data on 21 patients with symptomatic simple hepatic cysts were reviewed retrospectively. Cysts had a mean diameter of 9 cm (range: 7–15 cm). PAS was always performed under local anesthesia and US guidance. 25% of the volume was replaced with 95% ethanol and then completely aspirated after 20–30 minutes. No complications or deaths occurred. In all patients symptoms disappeared after treatment. In 15 out of 21 cases there was no evidence of residual cyst on US, computed tomography (CT) or magnetic resonance (MRI). In 6 patients with shorter follow-up, cysts showed a mean reduction in diameter of 50%. The mean follow-up was 18 months (range 6–60 months). We conclude that PAS is easy with low risk for the patients and with good long-term results; it should therefore become the procedure of choice for simple hepatic cysts.